THE STUDY OF CODE-SWITCHING IN TWIVORTIARE MOVIE - Benito Dira; Paskalina Dwi Intan Bui Lazar (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2019)
Language plays a critical role in engaging communication against each other in every community as it helps speakers to extend their comprehension and to provide insights, viewpoints, and perspectives in society. Individuals occasionally change from one language to another in bilingual societies around the world to fulfill communication requirements. This is regarded as code-switching. Thus, this current study focuses on the usage of code-switching specifically in an Indonesian film, Twivortiare. The researcher clarifies its investigation by implementing the qualitative descriptive method. The method, therefore, will be used to transcribe the data gathered by the researcher, and afterward, the next phase which is analyzing will begin. Data will be taken from conversations between the characters in the Twivortiare film that has been transcribed. In the analyzing phase, researchers applied a document analysis method which prioritizing on conversation analysis. The findings of the study reveal that the film is utilizing all of the three categories of code-switching: Intra-sentential, Inter-sentential, and Tag Switching. The language which is used is mostly from daily conversation. Some medical and financial terms are also employed because it is intertwined between the character's development and the plot of the story.